EVOLUTIONARY DYNAMIC MODEL OF POPULATION WITH NICHE CONSTRUCTION AND ITS APPLICATION RESEARCH - 李自珍 韩晓卓 李文龙 (Applied mathematics and mechanics, 2006)
Based on the theories and approaches in biomechanics, the mechanism and pattern of niche construction were discussed systematically. Through establishing the spatial pattern of niche and its measuring-fitness formula, and the dynamic system models of single- and two-population with niche construction, including corresponding theoretical analysis and numerical simulation on their evolutionary dynamics of population and the mechanism of competitive coexistence, the co-evolutionary relationship between organisms and their environments was revealed. The results indicate that population dynamics is governed by positive feedback between primary ecological factors and resource content. Niche construction generates an evolutionary effect in system by influencing the fitness of population. A threshold effect exists in single population dynamic system, in dynamic system of two competitive populations, niche construction can lead to alternative competitive consequences, which may be a potential mechanism to explain the competitive coexistence of species.